Solitary Fibrous Tumors of the Pleura - Ali, Maimona Iftikhar (Cureus, 2021)
Solitary fibrous tumors of the pleura (SFTP) are rare neoplasms. We present a case of a 53-year-old female presenting to the pulmonary clinic after an incidental finding of a right-sided chest wall tumor on a chest X-ray. A CT scan of the chest showed a pleural-based right upper lung mass; a biopsy of the mass was consistent with a solitary fibrous tumor.